ENERGY COOPERATION IN THE SUPPLY CHAIN AS AN INSTRUMENT OF POWER TRANSFORMATION IN INTERNATIONAL POLITICS: THE CASE OF AZERBAIJAN AND THE EUROPEAN UNION - Mijušković, Veljko; Ranković, Petar (National interest, 2025)
The paper is structured into six sections. The first section examines the geopolitical significance of energy security and the security of supply. Energy security has become an increasingly prominent factor in international politics, while diversification of supply is presented as a pathway to building greater resilience against external risks. The second section discusses how structural realism explains the underlying interests driving energy cooperation between the European Union and Azerbaijan, shaping the transformation of the security and energy architecture of Europe and the South Caucasus. The third section analyzes Azerbaijan’s geopolitical position and its historical role in Eurasian energy flows. The fourth section explores Europe’s decades-long dependence on Russian gas. The fifth section focuses on the development of bilateral cooperation between the European Union and Azerbaijan. Finally, the sixth section highlights the limitations and risks associated with energy cooperation between the two sides.
Keywords: Azerbaijan; European Union; Southern Gas Corridor; energy security; diversification of supply; structural realism